Selected legal issues of land cadastral surveying in Lithuania - Aksamitauskas, Vladislovas Česlovas; Grinevičiūtė, Kristina (Geodesy and Cartography, 2015)
This study is limited to the selected problematic aspects of cadastral surveys of land plots. Special attention is paid to the problem of on-site marking of the land plot boundaries. Authors have found that it determine imperative and complicated legal regulations. Cases where the act of marking-demonstration of the land plot boundaries is declared faulty in judicial practice are discussed. The problems of establishing the land plot boundaries are considered. Theoretical analysis is based on judicial practice. The advanced judicial practice demonstrates that immovable object cadastral surveys cannot correct legal ownership relationships.